Isoform- and ligand-specific modulation of the adhesion GPCR ADGRL3/Latrophilin3 by a synthetic binder - Szymon P. Kordon; Przemysław Dutka; Justyna M. Adamska; Sumit J. Bandekar; Katherine Leon; Satchal K. Erramilli; Brock Adams; Jingxian Li; Anthony A. Kossiakoff; Demet Araç (Nature Communications, 2023)
Adhesion GPCRs have numerous functions, ligands and isoforms. Here, Kordon et al. report synthetic antibodies that both modulate aGPCR signaling in an isoform-specific manner, and break receptor interactions in a ligand-specific manner